2003
DOI: 10.1016/s1535-6108(03)00301-5
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for cyclin D3 in lymphocyte development and T cell leukemias

Abstract: The D-type cyclins (cyclins D1, D2, and D3) are components of the core cell cycle machinery in mammalian cells. Cyclin D3 gene is rearranged and the protein is overexpressed in several human lymphoid malignancies. In order to determine the function of cyclin D3 in development and oncogenesis, we generated and analyzed cyclin D3-deficient mice. We found that cyclin D3(-/-) animals fail to undergo normal expansion of immature T lymphocytes and show greatly reduced susceptibility to T cell malignancies triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
342
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(355 citation statements)
references
References 51 publications
11
342
0
2
Order By: Relevance
“…Cyclin D3 was also found overexpressed in several human cancers (Ito et al, 2001;Wong et al, 2001;Hedberg et al, 2002;Pruneri et al, 2005) such as malignancies of the thymus (Filipits et al, 2002). Consistent with these results Sicinska et al (2003) established that cyclin D3-deficient mice displayed specific defects in the development of T lymphocytes. In addition to their growth-promoting functions, it was suggested that cyclin D3 plays a unique, nonredundant tissue-specific role such as in muscle differentiation (Kiess et al, 1995;Mariappan and Parnaik, 2005).…”
Section: Introductionsupporting
confidence: 82%
“…Cyclin D3 was also found overexpressed in several human cancers (Ito et al, 2001;Wong et al, 2001;Hedberg et al, 2002;Pruneri et al, 2005) such as malignancies of the thymus (Filipits et al, 2002). Consistent with these results Sicinska et al (2003) established that cyclin D3-deficient mice displayed specific defects in the development of T lymphocytes. In addition to their growth-promoting functions, it was suggested that cyclin D3 plays a unique, nonredundant tissue-specific role such as in muscle differentiation (Kiess et al, 1995;Mariappan and Parnaik, 2005).…”
Section: Introductionsupporting
confidence: 82%
“…39 Reinforcing this idea, CycE1 and CycE2 double knockout mice are also viable and show no major developmental problems. 40,41 However, minor cell cycle aberrations observed in cultured embryonic fibroblasts from these mice (CDK2KO, CycE1/E2DKO) seem to indicate an increased sensitivity to antiproliferative signaling during G1 phase, as they enter senescence earlier and show increased resistance to oncogene-induced transformation. Results presented here demonstrate that cell cycle arrest following p16 overexpression depends on the relative levels of cyclin/CDK2 complexes and p21/p27, suggesting a prevalence of CDK2 activity in the control of cell cycle progression.…”
Section: Discussionmentioning
confidence: 96%
“…Notch directly regulates D-type cyclins, which, in conjunction with cyclin-dependent kinase (cdk) 4 and cdk6 facilitate progression through the G 1 phase (Ronchini and Capobianco, 2000). In fact, in vitro and in vivo experiments indicate that upregulation of D-type cyclins is required for Notch-mediated transformation (Sicinska et al, 2003;Stahl et al, 2006). p27 is a cdk inhibitor that sequesters cyclin E to prevent cdk2 activation and S-phase progression (reviewed in Sherr and Roberts, 1999).…”
Section: Notch Regulates Cell-cycle Progressionmentioning
confidence: 99%